Factors Affecting Quality of Life and Longevity in the Elderly People in Phrae City, Thailand - Laddawan Daengthern; Somsak Thojampa; Kittisak Kumpeera; Chommanard Wannapornsiri; Roongtiva Boonpracom (JMIR Publications, 2020)
The purpose of this descriptive research was to study the factors that influence the quality of life (QOL) and longevity of the elderly in Thailand. The sample was made up of 280 elderly people in Phrae province, Thailand. The research found that (1) the QOL of the elderly in Phrae province was overall at a good level of 66.30%, (2) the factors that have significant influence on the QOL of the elderly at the p value = .01 are healing and exercise factors which are able to jointly predict the QOL of the elderly in Phrae Province by 12.2% (R2 = .122), and (3) from the structured interviews of 10 elderly people aged 80 years and older, it was found that diet, exercise, stress reduction, and healing are factors that allow the elderly to live for an average of 80 years which is above the average age of Thai people (the average age for men is 71.8 years old and for women is 78.6 years old).